Ultra-Sensitive Immuno-Sensing Platform Based on Gold-Coated Interdigitated Electrodes for the Detection of Parathion - Shalini Nagabooshanam; Souradeep Roy; Shikha Wadhwa; Ashish Mathur; Satheesh Krishnamurthy; Lalit Mohan Bharadwaj (Surfaces, 2022)
Pesticides are unavoidable in agriculture to protect crops from pests and insects. Organophosphates (OPs) are a class of pesticides that are more harmful because of the irreversible inhibition reaction with acetylcholinesterase enzyme, thereby posing serious health hazards in human beings. In the present work, a sensitive and selective immuno-sensing platform is developed using gold inter-digitized electrodes (Au-IDEs) as substrates, integrated with a microfluidic platform having the microfluidic well capacity of 10 µL. Au-IDE having digit width of 10 µm and gap length of 5 µm was used in this study. The surface morphological analysis by field-effect scanning electron microscopy (FE-SEM) and atomic force microscopy (AFM) revealed the direct information regarding the modification of Au-IDEs with anti-parathion (Anti-PT) antibodies. In SEM analysis, it was seen that the Au-IDE surface was smooth in contrast to the Anti-PT modified surface, which is supported by the AFM studies showing the surface roughness of ~2.02 nm for Au-IDE surface and ~15.86 nm for Anti-PT modified surface. Further, Fourier transform infra-red (FTIR) spectroscopic analysis confirms the immobilization of Anti-PT by the bond vibrations upon the successive modification of Au-IDE with -OH groups, amine groups after modifying with APTES, and the amide bond formation after incubation in Anti-PT antibody. Electrochemical impedance spectroscopy (EIS) was carried out for the electrochemical characterization and for testing the sensing performances of the fabricated electrode. The developed immuno-sensor provided a linear range of detection from 0.5 pg/L–1 µg/L, with a limit of detection (LoD) of 0.66 ng/L and sensitivity of 4.1 MΩ/ngL−1/cm2. The sensor response was also examined with real samples (pomegranate juice) with good accuracy, exhibiting a shelf life of 25 days. The miniaturized sensing platform, along with its better sensing performance, has huge potential to be integrated into portable electronics, leading to suitable field applications of pesticide screening devices.